2017
DOI: 10.3847/1538-3881/aa7138
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Study of Fourteen Low-mass Binaries

Abstract: New CCD photometric observations of fourteen short-period low-mass eclipsing binaries (LMB) in the photometric filters I, R and V were used for the light curve analysis. There still exists a discrepancy between radii as observed and those derived from the theoretical modelling for LMB in general. Mass calibration of all observed LMB was done using only the photometric indices. The light curve modelling of these selected systems were performed, yielding the new derived masses and radii for both components. We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…This effect was further studied by a light-curve solution. The observable difference in mid-eclipse times of spotted components was also outlined recently by Korda et al (2017).…”
Section: O-c Diagramsupporting
confidence: 61%
See 1 more Smart Citation
“…This effect was further studied by a light-curve solution. The observable difference in mid-eclipse times of spotted components was also outlined recently by Korda et al (2017).…”
Section: O-c Diagramsupporting
confidence: 61%
“…Barros et al (2013) showed that observed transit time variations in the hot-Jupiter WASP-10b system are also due to spot occultation features. Moreover, Korda et al (2017) tested the spot variability on the light curve of low-mass binaries and found a difference in mid-eclipse times of about 95 s. Recently, Zaire et al (2022) announced, that the well-known eclipsing binary system V471 Tau has the magnetically active K2 dwarf component, which might be responsible for driving the eclipse timing variations with predicted ∼ 35 yr activity cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Such metallicity independence of the massradius relation for low-mass stars is also frequently found in evolutionary models (see, e.g., Fig. 3 The reasons for the intrinsic spread in the observed massradius relation and the comparison to theoretical models have been and are still being investigated elsewhere (e.g., Feiden & Chaboyer 2012;Korda et al 2017;Tognelli et al 2018;Parsons et al 2018). As pointed out by Parsons et al (2018), this spread sets a lower limit on the error bars for the masses obtained with this method.…”
Section: Masses (M M−r )supporting
confidence: 57%
“…The reasons for the intrinsic spread in the observed mass-radius relation and the comparison to theoretical models have been and are still being investigated elsewhere (e.g., Feiden & Chaboyer 2012;Korda et al 2017;Tognelli et al 2018;Parsons et al 2018). As pointed out by Parsons et al (2018), this spread sets a lower limit on the error bars for the masses obtained with this method.…”
Section: Masses (M M−r )mentioning
confidence: 99%